Interactive Vocabulary Material for Indonesian EFL Senior High School Students - Akhmad Sutiyono; Muhamad Jejen Nurani; Aksendro Maximilian (Lentera: Jurnal Ilmiah Kependidikan, 2025)
This research aims to develop interactive vocabulary materials for Indonesian EFL High School students, therefore, the sample of this study was the tenth-grade students of vocational high school in Bandar Lampung. This study conducted as research and development design, which includes five stages, i.e, Analysis, Design, Development, Implementation, and Evaluation. Data were collected through interview with the English teachesr, students’ need analysis questionnaires, product validation questionnaires, and expert validation sheets. The results indicate that the developed materials, in terms of content (material and language), are categorized as very good, and the media aspects are also categorized as very good. These findings show that the interactive vocabulary materials are valid and appropriate to be used in the teaching and learning process.